TYPES OF ECONOMIC CONTRACTUAL LEGAL RELATIONS AT THE CURRENT STAGE OF DEVELOPMENT OF UKRAINE’S ECONOMY - Zhmur, Nataliia; Momotiuk, Veronika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: a comprehensive study of the concept of contract and analysis of types of economic contracts, contractual relationships that affect the development of Ukraine’s economy. To achieve this goal, general and special scientific research methods were used, in particular, such as: comparative law, system-structural method, as well as the method of analysis of current legislation. Results: the concept of economic agreement is analyzed, the types of economic agreements are studied, which serve as the main legal instrument, which is the relationship of business entities in market conditions. Discussion: economic contracts are endowed with their own specific characteristics that distinguish the legal category from contracts in other areas of law, in particular: special subject composition; economic connection; combination of property and organizational elements; the presence of special grounds for conclusion, content, etc.; the presence and need to take into account public interests.